Pengukuran Tingkat Kapabilitas Layanan Akademik Universitas Palembang Menggunakan Framework COBIT 5 - Muhammad Hafidh Putra Harti; Ricky Budiman; Desy Iba Ricoida (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Today, information technology has a very important role for companies to achieve their goals. Palembang University as an educational institution has a goal to be able to implement good higher education governance by utilizing information technology, especially in the field of academic services. Currently, the University of Palembang requires measurement of the implementation of information technology to support the institution's goals in providing effective and efficient academic services. In measuring the level of academic service capability, the Cobit 5 framework is used where the selected domain is Deliver, Service and Support (DSS), which is to ensure that services for supporting aspects are optimal or not. The results of measuring the level of academic service capability at the University of Palembang show that there is still a gap is the average value of the maturity level is 2.6.